Criminal liability for the establishment of a terrorist organization and participation in it - S. V. Chudin (Гуманитарные и юридические исследования)
Introduction. Terrorism does not disdain to incur huge casualties among innocent civilians, and terrorist organizations do not and cannot have just motives for their actions. Terrorist organizations not only kill innocent people, but also destroy historical heritage, cause discord in relations between peoples and countries, which can lead to the termination of the existence of the state, its dismemberment into “appanage principalities”, and even peoples.Materials and methods. The research is based on the analysis of texts by Russian and foreign scientists, which can be divided into two groups: historical and legal. It is very useful to use such methods as historical, systematic, logical and sociological, as well as comparative legal and statistical methods of scientific cognition when studying terrorist organizations. Also, when studying the topic of the article, the Constitution of the Russian Federation, international legal acts, federal legislation, court decisions and departmental regulations were used.Analysis. Terrorist crimes are crimes committed with the aim of creating panic; the purpose of which is to instill fear in society, create a sense of insecurity, and influence decision-making by state bodies.  Results. Countries with problems of unemployment and weak state institutions are the most favorable ground for the activities of terrorist organizations. The provision of a full-fledged education and the responsibility of the state to citizens are vital in solving the problem of eradicating terrorism. The norms of the Criminal Code of the Russian Federation on crimes of a terrorist nature are not always applied correctly, in addition, they are largely scattered in different parts. In this regard, it is necessary to further study the issues of qualification, it is necessary to improve legislation in the field of terrorism in order to achieve complete safety of life in the Russian Federation.